AN ANALYSIS OF TEST TAKER’S ERROR ON STRUCTURE AND WRITTEN EXPRESSION OF TOEFL TEST AT JLC (JIMS LANGUAGE COURSE) - Aa Qonaatun (FKIP, Universitas Banten Jaya, 2019)
The objective of the research are to find out “Which area do the test takers make error in Structure and Written Expression of the TOEFL Test”, and to find out “The describing of the test takers’ error of TOEFL test at JLC”, the writer conducted the research at JIMS Language Course. The populations of this research is TOEFL test takers at JLC, which consist of 30 participants from population grand total, the methodology used by the writer is content analysis and descriptive qualitative, which will find out about which area do the test takers make error in structure and written expression of the TOEFL test and to find out the describing of the test takers’ error of TOEFL test at JLC. The data is collected by analyzes the error of participants’ test. The test is structure and written expression, the data is analyzed by using the table of relative frequency. The result shows that the TOEFL test-takers at JLC still have poor ability in structure and written expression or could be said that the result of the research is poor. The Instructor explains structure and written expression clearly and then gave them a lot of exercise to make them understand.